To share or not to share? Evaluation of a strategic disclosure program for suicide attempt survivors. Issue 4 (21st April 2023) - Sheehan, Lindsay; Oexle, Nathalie; Bushman, Michael; Glover, LaToya; Lewy, Stanley; Armas, Silvia A.; Qin, Sang
Abstract: While suicide attempt survivors often choose to conceal their suicidal thoughts and behaviors to avoid stigma, concealment might also limit the support they receive. This study evaluated a peer-led strategic disclosure intervention for suicide attempt survivors ( N  = 38) who were randomized to either a 6-hour group disclosure intervention or waitlist control. Results showed a significant group-by-time interaction from baseline to post-intervention on two measures of self-stigma, depression, and self-esteem, but not for other variables. Effect sizes were medium to large. Findings suggest that suicide attempt survivors may benefit from interventions that address self-stigma and disclosure.